Parental Depressive Symptoms and Youth Internalizing and Externalizing Problems: The Moderating Role of Interparental Conflict - Breslend, Nicole Lafko (J Fam Violence, 2016)
The current investigation examined if interparental conflict (IPC), including psychological and physical violence, moderated the relationship between parental depressive symptoms and youth internalizing and externalizing problems, respectively, in a sample of youth with a parent with a history of Major Depressive Disorder (MDD). One hundred and eighty families with a parent with a history of MDD (M(age) = 41.96; 88.9% mothers) and a youth in the target age range of 9-to-15 years (49.4% females; M(age) = 11.46) participated. Findings indicated that IPC exacerbated the effect of parental depressive symptoms on internalizing, but not externalizing, problems for both males and females. Findings suggest that, in families with a parent who has a history of depression, parental depressive symptoms and IPC together have important implications for youth internalizing problems. Targeting improvement for both parent depressive symptoms and interparental conflict may directly lead to decreases in youth internalizing symptoms in the context of parental depression.